Carapace surface architecture facilitates camouflage of the decorator crab Tiarinia cornigera. (1st September 2016) - Sanka, Immanuel; Suyono, Eko Agus; Rivero-Müller, Adolfo; Alam, Parvez
Graphical abstract: Abstract: This paper elucidates the unique setal morphology of the decorator crab Tiarinia cornigera, and further presents evidence to that setal morphology promotes micro-organism nucleation and adhesion. The carapace of this crab is covered by clusters of setae, each comprising a hollow acicular stem that is enveloped by a haystack-like structure. Using computational fluid dynamics, we find that these setae are responsible for manipulating water flow over the carapace surface. Micro-organisms in the sea water, nest in areas of flow stagnation and as a result, nucleate to and biofoul the setae by means of chemical adhesion. Attached micro-organisms secrete extracellular polymeric substances, which we deduce must also provide an additional element of chemical adhesion to mechanically interlocked mesoscopic and macroscopic biomatter. By coupling physical and chemical methods for adhesion, T. cornigera is able to hierarchically decorate its carapace. Statement of Significance: Our paper brings to light the unique decorator crab carapace morphology of T. cornigera ; and furthermore evidences its function in micro-organism nucleation and adhesion. We show how this special carapace morphology directs and guides water flow to form nesting regions of water stagnation where micro-organisms can nucleate and adhere. In the literature, decorator crab carapaces are presumed to be able to mechanically interlock biomatter as camouflage using hook-like setal outgrowths. T. cornigera contrarily exhibits clusters of hay-stack like structures. By encouraging micro-organism adhesion to the carapace setae, T. cornigera is able to effectively attach biomatter using both chemical and physical principles of adhesion. T. cornigera essentially has a super-biofouling carapace surface, for at least micro-organisms. Our work will have an impact on researchers interested in biofouling, adhesion, biomedical and purification filter systems, and in the development of novel biomimetic surfaces with tailored properties.